Evaluation of soluble carbonic anhydrase IX as predictive marker for efficacy of bevacizumab: A biomarker analysis from the geparquinto phase III neoadjuvant breast cancer trial. Issue 3 (4th March 2019) - Janning, Melanie; Müller, Volkmar; Vettorazzi, Eik; Cubas‐Cordova, Miguel; Gensch, Victoria; Ben‐Batalla, Isabel; zu Eulenburg, Christine; Schem, Christian; Fasching, Peter A.; Schnappauf, Benjamin; Karn, Thomas; Fehm, Tanja; et al.
Abstract : We analyzed the predictive potential of pretreatment soluble carbonic anhydrase IX levels (sCAIX) for the efficacy of bevacizumab in the phase III neoadjuvant GeparQuinto trial. sCAIX was determined by enzyme‐linked immunosorbent assay (ELISA). Correlations between sCAIX and pathological complete response (pCR), disease‐free and overall survival (DFS, OS) were assessed with logistic and Cox proportional hazard regression models using bootstrapping for robust estimates and internal validation. 1, 160 HER2‐negative patient sera were analyzed, of whom 577 received bevacizumab. Patients with low pretreatment sCAIX had decreased pCR rates (12.1 vs . 20.1%, p = 0.012) and poorer DFS (adjusted 5‐year DFS 71.4 vs . 80.5 months, p = 0.010) compared to patients with high sCAIX when treated with neoadjuvant chemotherapy (NCT). For patients with low sCAIX, pCR rates significantly improved upon addition of bevacizumab to NCT (12.1 vs . 20.4%; p = 0.017), which was not the case in patients with high sCAIX (20.1% for NCT vs . 17.0% for NCT‐B, p = 0.913). When analyzing DFS we found that bevacizumab improved 5‐year DFS for patients with low sCAIX numerically but not significantly (71.4 vs . 78.5 months; log rank 0.234). In contrast, addition of bevacizumab worsened 5‐year DFS for patients with high sCAIX (81 vs . 73.6 months, log‐rank 0.025). By assessing sCAIX levels we identified a patient cohort in breast cancer that is potentially undertreated with NCT alone. Bevacizumab improved pCR rates in this group, suggesting sCAIX is a predictive biomarker for bevacizumab with regards to treatment response. Our data also show that bevacizumab is not beneficial in patients with high sCAIX. Abstract : What's new? While the addition of bevacizumab to neoadjuvant therapy can improve rates of pathological complete response (pCR) in different malignancies, a biomarker to identify patients likely to benefit from the combined therapy is lacking. In this study, serum soluble carbonic anhydrase IX (sCAIX) was identified as a marker for the selection of patients with early breast cancer responding to combined bevacizumab and neoadjuvant chemotherapy. Significant improvements in pCR rates were observed in patients with low sCAIX levels. The addition of bevacizumab further improved 5‐year disease‐free survival in low sCAIX patients, while having detrimental effects in patients with high sCAIX levels.